Low to negligible photoactivity of lake-water matter in the size range from 0.1 to 5 μm - Minella, Marco; Romeo, Fabio; Vione, Davide; Maurino, Valter; Minero, Claudio (Chemosphere (Oxford), 2011)
► Photochemical activity of lake water subject to different filtration steps. ► Most of the photoactivity accounted for by components smaller than 0.10 μm. ► Laser light scattering check of the filtration procedures (5, 0.45 and 0.10 μm). ► Filtration at 0.10 μm needed to remove all suspended particles. We found that the photochemical generation of reactive transients such as singlet oxygen and triplet states upon irradiation of different lake water samples is mostly accounted for by components smaller than 0.10 μm. Larger components often showed a much lower absorption and/or scattering of radiation compared with the smaller ones, with one exception where the minor to negligible photochemical activity of larger species was associated with significant radiation absorption/scattering. It is also shown that filtration of the lake water samples at 0.10 μm was able to effectively remove the suspended particles, differently from the usually suggested filtration at 0.45 μm.